2017
DOI: 10.1007/s40629-017-0014-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics in Hymenoptera venom allergy: current concepts and developments with special focus on molecular allergy diagnostics

Abstract: BackgroundThe high rate of asymptomatic sensitization to Hymenoptera venom, difficulty in correctly identifying Hymenoptera and loss of sensitization over time make an accurate diagnosis of Hymenoptera venom allergy challenging. Although routine diagnostic tests encompassing skin tests and the detection of venom-specific IgE antibodies with whole venom preparations are reliable, they offer insufficient precision in the case of double sensitized patients or in those with a history of sting anaphylaxis, in whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 71 publications
1
65
1
1
Order By: Relevance
“…Double positive results (e.g., to HBV and YJV) are common findings in venom extract-based allergy diagnostics. Previous studies conducted in Central Europe demonstrated that up to 47% of patients with anaphylactic sting reactions (n = 530) display double positivity to HBV and YJV [17]. Unfortunately, often this result does not reflect true sensitizations to different insects but is rather associated with the detection of clinically irrelevant cross-reactive IgE [10].…”
Section: Venom Extract-based Diagnostics: a Gold Standard With Limitamentioning
confidence: 96%
See 1 more Smart Citation
“…Double positive results (e.g., to HBV and YJV) are common findings in venom extract-based allergy diagnostics. Previous studies conducted in Central Europe demonstrated that up to 47% of patients with anaphylactic sting reactions (n = 530) display double positivity to HBV and YJV [17]. Unfortunately, often this result does not reflect true sensitizations to different insects but is rather associated with the detection of clinically irrelevant cross-reactive IgE [10].…”
Section: Venom Extract-based Diagnostics: a Gold Standard With Limitamentioning
confidence: 96%
“…Percentages of sequence identity (red triangles) and levels of 3-D structure similarities (green triangles) expressed by the root-mean square deviation (RMSD) of the atomic positions on the 3-D models are provided. RMSD values between 0-2 Å indicate a high-quality model with lower values indicating higher similarity to the template allergic patients (42-52%) [17], little or no IgE reactivity to CCD-free rVes v 2 has been reported in YJV allergic patients [33]. One explanation for the lack of peptide based cross-reactivity between YJ and HB hyaluronidases could be differences in their threedimensional structures and surface epitopes, which only display a low degree of similarity when analyzed by computational modeling [34,35].…”
Section: Component-resolved Diagnostics and Peptide Based Cross-reactmentioning
confidence: 99%
“…In accordance with previous studies on the natural course of sensitization to Hymenoptera venoms, our data suggest that sensitization to VV marker allergens peaks shortly after the sting, subsequently wanes, and may fall below the limits of detection within a couple of years. 5,7,21,26,27…”
Section: Recent Hymenoptera Stingsmentioning
confidence: 99%
“…5 A recent prospective study assessing the outcome of deliberate sting challenges, however, did not confirm an increased risk in asymptomatically sensitized subjects when compared to the general population. 7 IgE testing targeting single venom marker allergens was recently introduced for routine diagnostic assessment of Hymenoptera venom-allergic patients: 2,3 Up to 90% of patients allergic to Vespula venom (VV) are considered to be sensitized to rVes v 5 8,9 and just under 60% to rVes v 1. 7 IgE testing targeting single venom marker allergens was recently introduced for routine diagnostic assessment of Hymenoptera venom-allergic patients: 2,3 Up to 90% of patients allergic to Vespula venom (VV) are considered to be sensitized to rVes v 5 8,9 and just under 60% to rVes v 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation